Post-ischemic inflammation regulates neural damage and protection - Shichita, Takashi; Ito, Minako; Yoshimura, Akihiko (Frontiers in Cellular Neuroscience, 2014)
Post-ischemic inflammation is important in ischemic stroke pathology. However, details of the inflammation process, its resolution after stroke and its effect on pathology and neural damage have not been clarified. Brain swelling, which is often fatal in ischemic stroke patients, occurs at an early stage of stroke due to endothelial cell injury and severe inflammation by infiltrated mononuclear cells including macrophages, neutrophils, and lymphocytes. At early stage of inflammation, macrophages are activated by molecules released from necrotic cells (danger-associated molecular patterns (DAMPs)), and inflammatory cytokines and mediators that increase ischemic brain damage by disruption of the blood-brain barrier are released. After post-ischemic inflammation, macrophages function as scavengers of necrotic cell and brain tissue debris. Such macrophages are also involved in tissue repair and neural cell regeneration by producing tropic factors. The mechanisms of inflammation resolution and conversion of inflammation to neuroprotection are largely unknown. In this review, we summarize information accumulated recently about DAMP-induced inflammation and the neuroprotective effects of inflammatory cells, and discuss next generation strategies to treat ischemic stroke.